# Trig

posted by .

Compute inverse functions to four significant digits.
cos^2x=3-5cosx

rewrite it as..

cos^2x + 5cosx -3=0

now you have a quadratic, solve for cos x using the equation

cosx=(-5 -+ sqrt (25 +12)/2

## Similar Questions

1. ### Trig

prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2) then multiply that out 1-2CosX^2 + cos^4 - cosX^2 + 2cos^4 -cos^6 add that on the left to the cos^6, and …
2. ### trig question

Compute inverse functions to four significant digits. cos^2x=3-5cosx cos^2x + 5cosx -3=0 now you have a quadratic, solve for cos x using the equation cosx=(-5 -+ sqrt (25 +12)/2 the back of the book says .9987+2kpi and -.09987+2kpi …
3. ### trig

it says solve for all real solutions, compute inverse functions to 4 sigfigs. cos^2x=3-5cosx Devon, what grade level are these questions from?
4. ### Math - Solving for Trig Equations

Solve the following equation for 0 less than and/or equal to "x" less than and/or equal to 360 -- cos^2x - 1 = sin^2x -- Attempt: cos^2x - 1 - sin^2x = 0 cos^2x - 1 - (1 - cos^2x) = 0 cos^2x - 1 - 1 + cos^2x = 0 2cos^2x - 2 = 0 (2cos^2x/2)= …
5. ### Math - Solving Trig Equations

What am I doing wrong? Equation: sin2x = 2cos2x Answers: 90 and 270 .... My Work: 2sin(x)cos(x) = 2cos(2x) sin(x) cos(x) = cos(2x) sin(x) cos(x) = 2cos^2(x) - 1 cos(x) (+/-)\sqrt{1 - cos^2(x)} = 2cos^2(x) - 1 cos^2(x)(1 - cos^2(x))
6. ### Calc II

For the following question, we need to find the length of the polar curve: r= 2/(1-cosx) from pi/2 </= x </= pi dr/dx= -2sinx/(1-cosx)^2 therefore the length would be expressed as follows: the integral from pi/2 to pi of (sqrt)[(2/(1-cos))^2 …
7. ### Trigonometry

How do I solve these? 1) 2sinxcosx-cosx=0 2) cos^2(x)-0.5cosx=0 3) 6sin^2(x)-5sinx+1=0 4) tan^2(x)+tanx-12=0
8. ### Trigonometry

Write equivalent equations in the form of inverse functions for a.)x=y+cos è b.)cosy=x^2 (can you show how you would solve) a.) x= y+ cos è cos è = x-y theta = cos^-1(x-y) b.) cosy=x^2 cos(y) = x^2 y = Cos^-1(x^2)
9. ### Calc.

Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln y = x ln(cos x) (dy/dx)/(y)= ln(cos x) (dy/dx)= y ln(cos x) = (cos x)^x * (ln cos x) (dx/du)= x(cos x)^(x-1) * (-sin x) = - x sin(x)cos^(x-1)(x) (dy/dx)-(dx/du)= …
10. ### calculus

Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln y = x ln(cos x) (dy/dx)/(y)= ln(cos x) (dy/dx)= y ln(cos x) = (cos x)^x * (ln cos x) (dx/du)= x(cos x)^(x-1) * (-sin x) = - x sin(x)cos^(x-1)(x) (dy/dx)-(dx/du)= …

More Similar Questions